Fenologia de comunidade arbórea em um remanescente de floresta semidecidual na Bacia do Rio Grande - MG - Ridolfi, Stéphano Diniz (2017)
Phenology is the study of the cyclical events of living beings and their relation to the abiotic environment. This work aimed to study the correlation between phenological and meteorological events of a tree community in Nepomuceno, MG, and to select potential species for forest restoration, during two years. The fragment under study has 38 ha and the climate is classified as CwB. The sampling method was used to evaluate leaf phenophases, leaf regrowth, floral bud, flowering, green fruit and ripe fruit, and verify correlation with climatological data. All correlations between phenophases and months of the year were significant. The phenoapase presence of canopy had no correlation with any meteorological event. The foliar regrowth phenology had correlation with precipitation and average, minimum and maximum temperatures. The floral bud phenophase correlated with precipitation and sunshine, but with a delay time of three to four months between the meteorological event and the phenophasis. The flowering also had correlation with precipitation and insolation, with delay of five and three months respectively. The green fruit obtained correlation with the insolation with three months of delay. The phenophase mature fruit correlated with temperatures; The precipitation was correlated with the mature fruit, with a delay of four to five months. Twenty species were selected for the purpose of potentially providing seeds for forest restoration. In this work, we could conclude that there is a temporal logic in reproductive phenomena. It can also be concluded that the forest presents great potential for the collection of seeds, aiming at the forest restoration.